Backchannels Responses as Conversational Strategies in the Interaction of Indonesian Speakers in Interview Setting - Lisda Nurjaleka (REiLA)
In interpersonal communication, the listeners' role is as necessary as the speaker's. Backchannel is considered a universal behavior; it often occurs in the conversation to send a signal from the listener without claiming the floor. Linguists have identified backchannel responses in many languages and cultural differences regarding the backchannel's type, frequency, and placement. This study investigates the use of backchannel in Indonesian conversation by native speakers in interview settings. This mixed-method study combines a quantitative and qualitative study that examines the function and frequency of ten dyadic Indonesian native speakers in an interview setting. The sampling subject participant is 20 Indonesian native speakers with each gender; we selected ten people whose first language is the Indonesian language Each interview session took 20 to 30 minutes, totalling 4 hours, and 20 minutes of dialogue for the whole corpus. Based on the study findings, Indonesian native speakers often use nodding (each gender has the same frequency of around 42%) as a non-verbal backchannel. The current analysis suggests that nodding and facial expressions such as smiles, and laughter consider one of the listener responses in Indonesian conversation. Indonesian speakers' verbal backchannel does occur, but nodding occurs most frequently as a sign of the backchannel. The non-verbal behavior of nodding gives listening signals without bothering the speaker's utterance. The current study adds to our understanding of the listener's role in Indonesian conversation. These results contribute to intercultural understanding in the era of globalization.